2013
DOI: 10.6026/97320630009541
|View full text |Cite
|
Sign up to set email alerts
|

GMATo: A novel tool for the identification and analysis of microsatellites in large genomes

Abstract: Simple Sequence Repeats (SSR), also called microsatellite, is very useful for genetic marker development and genome application. The increasing whole sequences of more and more large genomes provide sources for SSR mining in silico. However currently existing SSR mining tools can’t process large genomes efficiently and generate no or poor statistics. Genome-wide Microsatellite Analyzing Tool (GMATo) is a novel tool for SSR mining and statistics at genome aspects. It is faster and more accurate than existed too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 8 publications
0
72
0
Order By: Relevance
“…GMATo comes with a Java graphical interface and is ready to execute immediately after downloading (Wang et al, 2013). GMATo results are presented as a table of SSR loci statistics.…”
Section: Software For Microsatellite Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…GMATo comes with a Java graphical interface and is ready to execute immediately after downloading (Wang et al, 2013). GMATo results are presented as a table of SSR loci statistics.…”
Section: Software For Microsatellite Developmentmentioning
confidence: 99%
“…Its results are in tabular form, giving a summary of different statistics, such as the frequency of a specific microsatellite type. However, some studies indicate that MISA may have mined redundantly in overlapped microsatellites (e.g., Wang et al, 2013; Hodel et al, 2016). …”
Section: Software For Microsatellite Developmentmentioning
confidence: 99%
“…All reads of seven accessions were also combined and used to assembly transcripts, which is called the 'pool' of transcripts. Functional annotation (Gene Ontology-GO and Kyoto Encyclopedia of Genes and Genomes-KEGG) was performed by means of sequence similarity (e-value cutoff of 10 -5 ) using Trapid (Van Bel et al, 2013), and SSRs were identified using GMATo (Wang et al, 2013) and SSRIT (http://www.gramene.org/db/markers/ ssrtool). Transcripts were aligned to Japanese apricot (Prunus mume) and peach (Prunus persica) genomes using Blast2go software (Conesa et al, 2005).…”
Section: De Novo Transcriptome Assembly and Functional And Structuralmentioning
confidence: 99%
“…We will then be able to mine the genomes in silico using software such as GMATo (Genome Microsatellite Analyzing Tool) (Wang et al 2013) or Phobos (Mayer 2006) for more robust microsatellite markers such as tetranucleotide repeats within these species. This will be particularly useful for the blue wildebeest which appears to need more informative microsatellite markers most urgently.…”
Section: Discussionmentioning
confidence: 99%